Tantangan Internalisasi Nilai-nilai Kristiani dalam Pembelajaran Pendidikan Agama Kristen: Studi pada Peserta Didik UPT SMAN 5 Tana Toraja - Yunita Tumonglo; Yosef Patandung (Institut Agama Kristen Negeri Toraja, 2026)
Abstract: The internalization of Christian values in Christian Religious Education (CRE) plays an important role in shaping students’ character. However, various personal and environmental factors often hinder this process. This study aims to analyze the challenges of internalizing Christian values among students at UPT SMAN 5 Tana Toraja. The research employed a qualitative approach with a case study design. The participants consisted of nine students and one Christian Religious Education teacher selected through purposive sampling. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The findings reveal that the internalization of Christian values, including love, honesty, forgiveness, self-control, humility, faithfulness, and sacrifice, has not been fully achieved. Internal challenges include difficulties in managing emotions, low self-control, a tendency to prioritize personal comfort, the need for social recognition, and weak spiritual commitment. External challenges include peer pressure, inadequate faith formation within the family, a lack of positive role models, and the influence of digital media. The novelty of this study lies in its in-depth identification of both internal and external factors affecting the internalization of Christian values among senior high school students. The study highlights the importance of collaboration among schools, families, and churches in fostering students’ Christian character development. Abstrak: Internalisasi nilai-nilai Kristiani dalam pembelajaran Pendidikan Agama Kristen (PAK) merupakan proses penting dalam pembentukan karakter peserta didik. Namun, berbagai faktor personal dan lingkungan sering menjadi hambatan dalam proses tersebut. Penelitian ini bertujuan menganalisis tantangan internalisasi nilai-nilai Kristiani pada peserta didik di UPT SMAN 5 Tana Toraja. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Informan terdiri atas sembilan peserta didik dan satu guru PAK yang dipilih secara purposive. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa internalisasi nilai kasih, kejujuran, pengampunan, pengendalian diri, kerendahan hati, kesetiaan, dan pengorbanan belum berlangsung secara optimal. Terdapat tantangan internal meliputi kesulitan mengelola emosi, rendahnya pengendalian diri, kecenderungan mengutamakan kenyamanan pribadi, kebutuhan akan pengakuan sosial, serta lemahnya komitmen spiritual. Tantangan eksternal mencakup tekanan teman sebaya, kurangnya pembinaan iman dalam keluarga, minimnya teladan lingkungan, dan pengaruh media digital. Kebaruan penelitian ini terletak pada identifikasi mendalam mengenai tantangan internal dan eksternal yang memengaruhi internalisasi nilai-nilai Kristiani pada peserta didik SMA. Penelitian ini menegaskan pentingnya sinergi antara sekolah, keluarga, dan gereja dalam mendukung pembentukan karakter Kristiani peserta didik.